Meningkatkan Kemampuan Literasi dan Berhitung bagi Siswa Kelas Rendah SDN Durung Bedug - Iffat, Chanifatul; Maghfiroh, Filzah Batrisyiyah; Haque, Zanneta Arinil (Lembaga Yasin AlSys, 2024)
The aim of this research is to find out how to improve literacy and numeracy skills for lower class students at SDN Durung Bedug. Then the results of the research we obtained are presented in the form of articles to fulfill the assignment for the Educational Evaluation course. This research was conducted at SDN Durung Bedug which is located at Jl. Durung Bedug, New Bedug, Lebo, District. Sidoarjo, Sidoarjo Regency, East Java 61223. This research uses qualitative methods by coming directly to the research location then observing interviews, namely questions and answers with the school, then we analyze the results of the research to produce articles. Researchers also use literature study methods, by collecting library data, reading and taking notes, and processing research materials. With the research we conducted, it can be concluded that reading or literacy and numeracy skills in the lower grades are very important and must be possessed by a student. Without literacy and numeracy skills, it will hinder students' progress in the learning process. Literacy and numeracy skills have a big impact on students forever. By having this ability, students can understand and absorb every word or explanation the teacher says in class and can understand every question they face, so that students will easily understand the questions and minimize misunderstandings in understanding and working on the questions. Literacy and numeracy skills can also hone students' abilities in thinking critically, making decisions, and understanding information from reading.